Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Equation is x² - 2ax -(4b² -a²) =0
rearrange the terms,
(x² -2ax +a²) = 4b²
⇒(x -a)² = (2b)²
⇒(x -a) =2b or, (x -a) = -2b
⇒x = (a +2b) or x= (a -2b)
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts